Сон Макара: святочный рассказ / В. Г. Короленко - Короленко Владимир Галактионович (Удмуртия, 2003)
Экземпляры: ХР (20180507) / Инвентарный номер: 38222 / Цена: 50 / Сис.шифр: С(Удм) / Авт.знак: К 68 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1